REKAYASA CNC TURNING SEBAGAI MEDIA PEMBELAJARAN CNC - Bambang Setiyo Hari Purwoko (Jurnal Kependidikan, 2016)
ABSTRACTEngineering CNC Turning aims; (1) produce a prototype, which is capable of a teaching aids, and resources of CNC programming. Engineering conducted following the procedures Research and Development (R D) expressed Borg and Gall. Starting with a needs study of teaching aids/media of CNC programming; defining products (define); designing a system and form (design); develop products and test its performance (develop); and the revision/ improvement of product performance (revise). Results of the research is a prototype CNC Turning as taching aids/media, which is capable of; (1) demonstrate the operation of a CNC machine (input/editing program), program execution (such as graphic toolpath and the workpiece machining process); (2) providing experience operate the CNC machine that is not scary (prototype has a small size, mini); (3) demonstrate command codes which are the main learning materials in CNC programming